IMPROVING STUDENTS ENGAGEMENT IN SPEAKING THROUGH THINK- PAIR-SHARE TECHNIQUE (A Classroom Action Research at Mahad al-Jamiah IAIN Pontianak) - Adawiyah, Jazilatul (English Language Education Study Program, 2021)
This study aimed to improve Students engagement in speaking activities through Think-Pair-Share (TPS) technique. The TPS was used in this classroom action research (CAR) as a technique of teaching speaking in English under collaborative learning strategy. The study was conducted at Mahad al-Jamiah (boarding) IAIN Pontianak which involved twenty- five students as participants. Additionally, this study aimed to learn about the problem faced in the learning process through observations and reflections. The data of the research were qualitative and quantitative analysis. They were collected through classroom observations, field note takings and recordings. To analyze the data, the researcher used qualitative analyses by interpreting the data to find clear pictures of the students engagement. However, quantitative analyses were also used to support the interpretation. Through three cycles of planning, acting, observing, and reflecting procedures, it was found that the students engagement improved when the learners were actively participated in the implementation of Think-Pair-Share technique. The research findings showed that in the first cycle 41.6 %, the second cycle 60 %, and the third cycle was 75.6 %.